On minimal non- MSP -groups - Guo, P.; Zhang, Xirong (Ukrains’kyi Matematychnyi Zhurnal, 2011)
A finite group $G$ is called an $MSP$-group if all maximal subgroups of the Sylow subgroups of $G$ are Squasinormal in $G$. In this paper, wc give a complete classification of those groups which are not $MSP$-groups but whose proper subgroups are all $MSP$-groups.